Elevated Controlling Nutritional Status (CONUT) Score is Associated with Poor Long-term Survival in Patients with Low-grade Soft-tissue Sarcomas Treated with Surgical Resection. Issue 10 (October 2019) - Liang, Yao; Hou, Tao; Que, Yi; Zhao, Baiwei; Xiao, Wei; Zhang, Xing; Zhou, Zhiwei
Abstract: Background: Several studies have examined the Controlling Nutritional Status (CONUT) score, which is a screening tool for nutritional status and an effective biomarker for patient survival after cancer treatment. However, its role in soft-tissue sarcoma (STS) remains unknown. Because of the lack of predictive markers for survival in patients with STS, we aimed to determine the CONUT score's association with survival. Questions/purposes: (1) Is there a relationship between the CONUT score and clinicopathologic characteristics such as tumor size, tumor location, pathological grade, and advanced stage based on the American Joint Committee on Cancer (AJCC) guidelines? (2) Is the CONUT score associated with disease-free survival (DFS) and overall survival (OS) in patients treated surgically for STS, even when compared with other systemic inflammatory response markers? Methods: Between 1999 and 2016, 769 patients underwent R0 resection for STS at our institution. Adequate medical records and available followup data were required for inclusion in this study. Exclusion criteria were synchronous inflammatory diseases, unplanned excision, and neoadjuvant therapy. There were 658 patients (86%) who fulfilled all criteria. The minimum followup time was 24 months (median, 103 months; range, 61-147 months). The median age of the patients was 43 years (range, 5-85 years), and 265 patients (40%) were women. All patients had Stage I to IV tumors according to the 8 th edition of the AJCC staging system. The grade classification was determined to be G1 in 130 patients (20%), G2 in 304 (46%), and G3 in 201 (31%). The CONUT score was calculated based on the serum albumin concentration, total peripheral lymphocyte count, and total cholesterol concentration. The score ranged from 0 to 12, with higher scores indicating worse nutritional status. The patients were classified into two groups according to a receiver operating characteristic curve analysis: the high (≥ 2) and low (0 or 1) CONUT score groups. There were 435 patients in the low CONUT score group and 223 in the high CONUT score group. We tested for an association between the CONUT scores and gender, age, tumor diameter, tumor depth, tumor grade, and AJCC stage using the chi-square and Fisher's exact methods. We also compared the strength of the association between postoperative survival and the CONUT scores, neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio (PLR) using multivariate Cox proportional hazard model analyses. Results: High CONUT scores were associated with large tumor size (odds ratio [OR], 1.47; 95% CI, 1.06-2.04; p = 0.020), deep tumor location (OR, 1.66; 95% CI, 1.17-2.36; p = 0.004), high tumor grade (OR, 2.54; 95% CI, 1.56-4.14; p = 0.001), and advanced AJCC stage (OR, 1.86; 95% CI, 1.14-3.02; p < 0.001). The low CONUT score group exhibited a higher 5-year OS rate and longer OS than the high CONUT score group (82% versus 65%; odds ratio, 2.45; 95% CI, 1.27-4.72; p < 0.001; 81 versus 64 months, Z = -2.56; p < 0.001). A multivariate analysis indicated that an elevated CONUT score was an independent predictor of OS (hazard ratio [HR], 1.86; 95% CI, 1.47-4.14; p < 0.001) and DFS (HR, 1.63; 95% CI, 1.26-2.11; p < 0.001), but the NLR and PLR were not. In an individual subgroup analysis, the CONUT scores were associated with OS and DFS in the tumor diameter (< 5 or ≥ 5 cm) subgroup, tumor depth (superficial or deep) subgroup, tumor grade (G1 and G2) subgroup, and AJCC stage (I/II or III/IV) subgroup, but not in the G3 subgroup (p = 0.051 and p = 0.065). Conclusion: High CONUT scores were independently associated with aggressive tumor behavior and unfavorable survival for patients with low-grade, but not high-grade, resected STS. If these findings can be substantiated in larger studies, the CONUT score might be useful for predicting survival and help to develop new treatment strategies for nutrition interventions. Level of Evidence: Level III, therapeutic study.